Simulation - Ross, Sheldon M. (San Diego : Academic Press, 2013)
The 5th edition of Ross's Simulation continues to introduce aspiring and practicing actuaries, engineers, computer scientists and others to the practical aspects of constructing computerized simulation studies to analyze and interpret real phenomena. Readers learn to apply results of these analyses to problems in a wide variety of fields to obtain effective, accurate solutions and make predictions about future outcomes. This latest edition features all-new material on variance reduction, including control variables and their use in estimating the expected return at blackjack and their relation to regression analysis. Additionally, the 5th edition expands on Markov chain monte carlo methods, and offers unique information on the alias method for generating discrete random variables. By explaining how a computer can be used to generate random numbers and how to use these random numbers to generate the behavior of a stochastic model over time, Ross's Simulation, 5th edition presents the statistics needed to analyze simulated data as well as that needed for validating the simulation model. New to this Edition: Additional material on variance reduction, including control variables and their use in estimating the expected return at blackjack and their relation to regression analysisAdditional material and examples on Markov chain monte carlo methods Unique material on the alias method for generating discrete random variables. Additional material on generating multivariate normal vectors"R" software code package on the website the correlates to the specific material in the book.
Machine generated contents note: Preface; Introduction; Elements of Probability; Random Numbers; Generating Discrete Random Variables; Generating Continuous Random Variables; The Discrete Event Simulation Approach; Statistical Analysis of Simulated Data; Variance Reduction Techniques; Statistical Validation Techniques; Markov Chain Monte Carlo Methods; Some Additional Topics; Exercises; References; Index.
Includes index.
Title from publisher's Web site; (ScienceDirect; viewed on Oct. 25, 2012).
Includes bibliographical references and index.
Keywords: Computer simulation; Computer simulation